Soft Life vs. Hard Life Mentality: Different Psychological Perspectives on Seeking Happiness - Anana, Marvina (Psikologiya Journal, 2025)
The concepts of Soft Life and Hard Life are two approaches to life that are gaining increasing attention in contemporary psychology, particularly in relation to the search for happiness, meaning in life, and psychological well-being. The Soft Life Mentality focuses on comfort, luxury, and stress avoidance, which in the short term can increase emotional calm and reduce anxiety. However, if overly dominated by a comfort orientation, this lifestyle risks creating a sense of emptiness and a loss of deeper meaning in life. In contrast, the Hard Life Mentality emphasizes struggle, perseverance, and hard work as the path to significant achievement. This approach often produces a more lasting sense of satisfaction and eudaimonic happiness, but also carries the risk of stress, burnout, and physical and mental health disorders if not balanced with self-healing. This study used qualitative methods with literature analysis of various academic sources regarding the relationship between these two mentalities and quality of life, coping mechanisms, and theories of hedonic and eudaimonic happiness. The results indicate that a balance between Soft Life and Hard Life is key to achieving more holistic happiness. Integrating the two not only improves an individual's emotional well-being but also strengthens social relationships and builds a foundation for more sustainable, long-term happiness..